CULTURAL HYBRIDIZATION IN THE DIGITAL AGE: RECONSTRUCTING IDENTITY ACROSS TRANSNATIONAL MEDIA SPACES - Abdul Rahman (Social Studies and Humanities Journal (SOSHUM), 2025)
Fundamental transformations in the global communication landscape have shifted cultural interaction paradigms toward fluid transnational digital media spaces. Amidst the dominance of global platforms and massive internet penetration, tensions have emerged between cultural homogenization and the potential for emancipatory hybridization. This study aims to analyze how the interaction between transnational media exposure, algorithmic structures, and local contexts shapes the process of identity reconstruction in digital spaces. This research employs a systematic narrative review approach, analyzing literature from Scopus and Web of Science databases published within the last ten years. The findings indicate that digital platforms function as socio-technical fields where cultural visibility and legitimacy are produced through non-neutral algorithmic curation. The phenomenon of "staged authenticity" emerges as a consequence of identity commodification within the persona economy. However, digital spaces also serve as a "Third Space," enabling marginalized communities to mobilize counter-narratives and resistance against global hegemony. Cultural hybridization in the digital age is an ambivalent process involving the risk of identity commodification alongside opportunities for subaltern agency. A digital constitutionalism framework is required to ensure cultural diversity within the transnational media ecosystem.